PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT DIRGA SATRIA PRATAMA - Loy, Delvin; Khoiri, M. (SCIENTIA JOURNAL, 2022)
This study was conducted determine the effect of discipline and work motivation onemployee performance at PT Dirga Satria Pratama. This research is a quantitative studyand data obtained through questionnaires. Population this study is total number ofemployees . The number samples this study were 110 people. The questionnaire distributedby researchers to respondents was 110 respondents. Data collection technique used issaturated sampling technique the sample taken a whole in the population. Primary datacollected from questionnaire result distributed. Result in this study indicate the disciplinedvariable has positive effect of 0.421 and significance of 0,000 < 0,05 and tcount has value5.395 > ttable 1.98238 on employee performance variables at PT Dirga Satria Pratama.Work motivation variable has positive effect of 0.349 and significance of 0,000 < 0,05 andtcount value of 5.182 >ttable 1.98238 on employee performance variables at PT Dirga SatriaPratama. The disciplinary and work motivation variables together have positive andsignificant effect on employee performance variables at PT Dirga Satria Pratama andsignificance of 0,000 < 0,05 and Fcount 101.721 > ttable 3.08.